Tokoh Pro dan Kontra Atas Undang-Undang Perkawinan di Indonesia dalam Perspektif Praktik Sosial Pierre Bourdiue - Hani Nadiya Putri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Indonesian Marriage Law Number 1 of 1974 is a product of Islamic Family Law that emerged through a highly complex social and political process, involving intense debate between the state, religious groups, and civil society. Its introduction has generated both pros and cons from various figures, from religious scholars, academics, women's activists, to socio-religious organizations. This study aims to analyze the attitudes or positions of pro and contra figures towards the Indonesian Marriage Law using Pierre Bourdieu's theory of social practice. This study uses a qualitative approach with an interpretative-critical paradigm, by placing the concepts of habitus, capital (cultural, social, symbolic, and political), and arena as the main analytical tools. Data are analyzed by tracing the social background, education, power networks, and symbolic authority of the figures in the realm of family law legislation. The research findings show that the pros and cons of the Marriage Law are not solely based on differing normative or theological perspectives, but rather are social practices shaped by the structural positions of actors within the political-legal and religious arenas. Pro-Islamic figures, such as women's activists, academics, and progressive clerics, generally possess a modernist habitus and cultural and symbolic capital that encourages reform of family law. Conversely, anti-Islamic figures, particularly those from traditional clerics and Islamic politicians, exhibit a conservative fiqh habitus with strong symbolic capital from the clerics, thus viewing state regulations as a form of intervention in Islamic legal authority. These findings confirm that the formation of family law in Indonesia is the result of dynamic power relations and social contestation, not simply a product of legal-formal norms